Association of serum irisin levels with anthropometric, biochemical and atherogenic indices in healthy adults - Ommati, Nazanin; Nikniaz, Leila; Mahdavi, Reza (Progress in Nutrition, 2019)
Objective: Irisin, a myokine mostly expressed by muscle, is proposed to increase energy expenditure and reduce obesity and metabolic disorders. So, we evaluated the association between serum irisin levels and various anthropometric, biochemical, and atherogenic indices. Methods: This cross-sectional study was conducted on 90 apparently healthy males and females, aged 20-55 years, selected with simple random sampling. Anthropometric and atherogenic indices, dietary intake, physical activity levels, serum irisin levels, lipid profile, and fasting blood sugar (FBS) of the subjects were measured. Results: Median Irisin level was 1200 (500-8600) pg/ml which was higher in women than men (1250.00 (800-8600) VS. 1050 (500-7700)). In multivariate linear regression analysis, after controlling for potential confounders (age, total energy intake and physical activity), irisin levels were significantly associated with BMI (r=-0.214; P=0.003), waist circumference (WC) (r=-0.002; P=0.004), hip circumference (HC) (r=-0.245; P=0.004), waist-to-height ratio (WHtR) (r=-0.223; P=0.005), Body Roundness Index (BRI) (r=-0.214; P=0.008), Abdominal Volume Index (AVI) (r=-0.189; P=0.009), and Body Adiposity Index (BAI) (r=-0.207; P=0.046). In male subjects, it was significantly associated with BMI (r=-0.182, P=0.049), HC (r=-0.295; P=0.005), waist-to-hip ratio (WHR) (r=0.279; P=0.038) and BAI (r=-0.418; P=0.001), while in females with BMI (r=-0.268; P=0.005), WC (r=-0.236; P=0.030), WHtR (r=-0.223; P=0.047), and AVI (r=-0.226; P=0.047). No significant association was observed between irisin and biochemical and atherogenic indices. Conclusions: In the present study, irisin level was significantly associated with BMI, WC, HC, WHtR, BRI, and BAI. However, further studies are needed to clarify the role of irisin in obesity and its comorbidities.